Periodontal status in growing patients with unilateral cleft lip and palate - Wyrębek, Beata; Górska, Renata; Cudziło, Dorota; Plakwicz, Paweł (Journal of Stomatology, 2017)
Aim of the study. To evaluate differences in periodontal parameters and oral hygiene between cleft and control sides in growing patients with unilateral cleft. Materials and Methods: 15 patients, aged 10 to 18 years, with unilateral cleft lip and palate. Evaluation of probing pocket depth (PPD), clinical attachment level (CAL), gingival recession (REC), vestibule depth (VD), keratinized gingiva (KG), presence of plaque (PCR) and bleeding on probing (BoP) for eight maxillary anterior teeth were performed. Types of fraena and mucosa deformities were also evaluated. Results. Significant differences for PD (but not for CAL) were found only at some surfaces of lateral incisors and canines. Keratinized gingiva was significantly narrower at lateral incisors, canines and first premolars on the cleft side (mean values were: 2.8 mm and 5.4 mm for lateral incisors, 2.7 mm and 3.9 mm for canines, 3.1 mm and 4.7 mm for first premolars, respectively for the affected and the control side). Significantly shallower vestibule at central and lateral incisors was found at some group of teeth (mean values were: 7.0 and 9.2 mm for central incisors, 8.6 and 11.6 mm for lateral incisors, respectively for the affected and control side). Due to tissue malformations it was difficult to assess the upper labial fraena. High scores were recorded for PCR and BoP both on the cleft and the control side. Conclusions. Malformations of soft tissues caused by cleft and previous surgical procedures negatively affected periodontal parameters on the cleft side. It is requisite to introduce periodontal assessment into comprehensive approach in children with clefts to control development of periodontal disease.